2005
DOI: 10.1677/joe.1.06082
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor subtype expression in the human heart: differential expression by myocytes and fibroblasts

Abstract: In acromegaly, somatostatin receptor ligands (SRLs) can ameliorate left ventricular hypertrophy (LVH) and their use is associated with demonstrable improvements in various parameters of cardiac function. It remains unclear as to whether these beneficial effects are principally attributable to falling GH and IGF-I levels, or whether SRLs exert independent direct effects on the heart via somatostatin receptors. To help address this issue, we have sought to investigate somatostatin receptor expression in human he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…To date, the majority of research on somatostatin has focused on hormonal regulation in gastrointestinal and nervous systems. More recent evidence has suggested the presence of the somatostatin receptors in both human hearts and H9c2 cardiac muscle cells (10,30). Somatostatin was found to suppress atrial contractile function and blunt atrioventricular conduction (1).…”
mentioning
confidence: 99%
“…To date, the majority of research on somatostatin has focused on hormonal regulation in gastrointestinal and nervous systems. More recent evidence has suggested the presence of the somatostatin receptors in both human hearts and H9c2 cardiac muscle cells (10,30). Somatostatin was found to suppress atrial contractile function and blunt atrioventricular conduction (1).…”
mentioning
confidence: 99%
“…Using a similar approach, other investigators have been unable to detect SRIF1B (SSTR5) [38] or SRIF2B (SSTR4) [30] receptor expression in adult murine heart. In a study by Smith and co-workers [33], human cardiomyocytes were found to express only SRIF1A (SSTR2) and SRIF2A (SSTR1) receptors, in contrast to human cardiac fibroblasts, which in addition to these subtypes, expressed SRIF1B (SSTR5) and SRIF2B (SSTR4) but not SRIF1C (SSTR3) receptors. Rodent and human myocardium clearly differ in regard to SRIF receptor subtype expression, since we have found that SRIF1A (SSTR2) and SRIF2A (SSTR1) are the least abundant receptors expressed in adult rat ventricular cardiomyocytes.…”
Section: Hypertrophic Parametersmentioning
confidence: 95%
“…Left ventricular hypertrophy in acromegaly is characterized not only by hypertrophy of cardiomyocytes, which are terminally differentiated and unable to proliferate, but also disproportionate proliferation of cardiac fibroblasts and accumulation of fibrillar collagen contributing to impaired diastolic function [13,14]. In view of the presence of SRIF (SSTR) receptors on human cardiac fibroblasts [33] a direct inhibitory influence of SRIF-14 analogues on fibroblast proliferation cannot be discounted at present.…”
Section: Hypertrophic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Octreotide has anti-secretive and anti-proliferative effects by binding and activating somatostatin receptor subtypes 2 and 5 [5]. These receptors are expressed in human cardiac myocytes and fibroblasts [11]. Octreotide improves LV hypertrophy, LV function and ventricular arrhythmia in patients with acromegaly [12][13][14].…”
mentioning
confidence: 99%